Exploration of Learning Outcomes Through Preventive Efforts to Prevent Adolescent Academic Procrastination in Pasca Pandemi Covid-19 - Fitriana, Fitriana; Minarsi, Minarsi; Hansein Arif Wijaya; Gina Fauzia; Rofiazka Fahmi Huda (International journal of technology and education research, 2023)
Teenagers as agents of change in human resources for the better. This condition will not be achieved if teenagers do not carry out their roles and tasks optimally, one of which is by achieving good learning outcomes by preventing academic procrastination. The aim of this research is to explore learning outcomes through preventing adolescent academic procrastination after the Covid-19 pandemic. Academic procrastination is the behavior of delaying or completing school or college assignments. Undecided students are more likely to fail academically. Academic procrastination is the behavior of someone who wants to delay completing a task. As a result, students become lazy and often experience academic failure. Exploratory studies of learning outcomes to prevent academic procrastination can be carried out by paying attention to physical condition, motivation, self-efficacy and self-awareness, parenting patterns, the environment, as well as guidance from guidance and counseling teachers at school, with self-instruction counseling treatment, cognitive restructuring, cognitive behavior modification, behavior contracts, self-regulated learning, positive reinforcement techniques, and others.